2015
DOI: 10.1371/journal.pone.0125465
|View full text |Cite
|
Sign up to set email alerts
|

TB Treatment Delays in Odisha, India: Is It Expected Even after These Many Years of RNTCP Implementation?

Abstract: BackgroundIn India, the Revised National TB Control Programme (RNTCP) envisages initiation of TB treatment within seven days of diagnosis among smear-positive patients. After nearly two decades of RNTCP implementation, treatment delays are usually not expected.ObjectivesTo determine the proportion of sputum smear-positive TB patients who were initiated on treatment after seven days and their associated risk factors.MethodsThe study was conducted in Cuttack and Rayagada districts of Odisha. It was a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…In addition, we analyzed "timely HIV diagnosis" as follow: "early" when CD4þ T-cell count was 500 cells/mm 3 or a clinical stage of HIV infection was A1 or B1, and "late" with CD4 < 500 cells/mm 3 or all the remaining clinical stages. 4.…”
Section: Delay In Tb Treatment Initiation Due To the Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we analyzed "timely HIV diagnosis" as follow: "early" when CD4þ T-cell count was 500 cells/mm 3 or a clinical stage of HIV infection was A1 or B1, and "late" with CD4 < 500 cells/mm 3 or all the remaining clinical stages. 4.…”
Section: Delay In Tb Treatment Initiation Due To the Systemmentioning
confidence: 99%
“…1 Risk factors that have been reported as associated with prolonged delay (>35 days from onset of symptoms to receipt of TB treatment) in TB diagnosis in patients co-infected with HIV are unemployment, alcohol consumption, crowding index, seeking prior treatment, cotrimoxazole treatment, and World Health Organization (WHO) stage 4 disease. 2 In addition, HIV-positive TB patients have higher risk for delay in TB treatment compared to HIVnegative TB patients, 3 and for delay in HIV treatment initiation due to lower baseline CD4 cell count, TB drug intolerance, nondisclosure of HIV infection, 4 immune reconstitution inflammatory syndrome, 5,6 and drug interactions of concomitant use of TB and HIV treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four qualitative studies mentioned self-perception of health, and unconvinced of the diagnosis and the need for TB treatment, and the perceived low effectiveness of TB treatment led to a delay in TB treatment initiation [44,94,117,139]. We also found that retreatment cases were more likely to delay TB treatment initiation [92][93][94][95][96].…”
Section: Treatment Delaymentioning
confidence: 63%
“…The DOTS-based RNTCP has been remarkably successful in achieving the global targets of detecting 70% of the estimated TB cases and curing 85% of them [ 3 , 4 ]. The RNTCP since its inclusion as a national TB control program has given good results, as evident by the detailed WHO global annual reports, yet the TB elimination looks a far-sighted dream [ 4 , 5 ]. There are a number of issues that are hampering the ongoing RNTCP progress in India.…”
Section: Essaymentioning
confidence: 99%